Production linkages, technological intensities and economic performance : small and medium enterprises in Malaysian manufacturing - Mohd Rosli Mohamad; Rajah Rasiah; Puvanesvaran Sanjivee (Routledge, 2011)
This paper examines the impact of proximate domestic sourcing on productivity, exports andatechnological upgrading in small and medium enterprises (SMEs) in electric-electronics, textiles-garments, automotives and wood products industries in Malaysia. The results show that the intensity of backward subcontracting in the domestic economy was important in domestic and export intra-industry purchases. The significant technological variables were that less-integrated firms showed higher intensities than more-integrated firms. Econometric results show that technological intensity is positively correlated with productivity and exportorientation; this infers that technology matters in economic performance. The Probit estimations confirm that domestic supplies matter in labour productivity and exportintensities, but not in technological intensities. Low export-intensities need not discourage technological upgrading if inward-oriented firms operate as subcontractors supplying exporters. Governments should be encouraged to examine the nexus between suppliers, buyers and economic performance to stimulate national inter-firm production synergies to increase competitiveness by domestic firms.